The Periphery of the Euro : Monetary and exchange rate policy in CIS countries - De Lombaerde, Philippe; Vinhas de Souza, Lúcio. (Aldershot, Hants ; Burlington, VT : Ashgate, 2006)
This book analyses the monetary and exchange rate policies in Eastern European countries not covered by the current EU enlargement process. Specifically, the book examines the major CIS countries: Belarus, Kazakhstan, Russia and the Ukraine. (The new Eastern European EU members are also frequently referenced for comparison purposes.) Current and prospective monetary policy options are considered, and the applicability of the EU monetary integration experience for the CIS countries and the prospects of a monetary re-unification around the Russian Federation are assessed. This is the first book to formally deal with many of these questions.
Includes bibliographical references and index.
rpm 19/09/16
Loans
Keywords: Monetary policy; Monetary unions